2022
DOI: 10.3389/fonc.2022.1025930
|View full text |Cite
|
Sign up to set email alerts
|

18F-PSMA-1007 PET/CT-derived semi-quantitative parameters for risk stratification of newly diagnosed prostate cancer

Abstract: PurposeThis study aimed to assess the value of 18F-PSMA-1007 positron emission tomography/computed tomography (PET/CT)-derived semi-quantitative parameters of primary tumor for risk stratification of newly diagnosed prostate cancer (PCa).MethodsSixty patients referred for 18F-PSMA-1007 PET/CT imaging for primary PCa were retrospectively analyzed and classified into the low-intermediate-risk (LIR) or high-risk (HR) group. The maximum standardized uptake value (SUVmax) of primary tumor, prostate total lesion PSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“… 29 , 30 However, Mayer et al 31 reported that histology-based TV is related to the GS (r = 0.498, P = 0.0098), and Baba et al 9 suggested that the optimal TV cut-off value for predicting BCR was 2.8 cc (AUC: 0.690). Moreover, Castiglione et al 32 concluded that for high-risk patients with PCa, a TV >6.29 cc (AUC: 0.722) leads to CF, and Dong et al 33 reported that the optimal cut-off value for identifying the best maximum standardized uptake value (SUV max ) for high-risk patients with PCa was 9.61 (AUC: 0.828). Furthermore, Jiao et al 34 established and prospectively verified that the optimal SUV max cut-off value for discriminating clinically significant PCa from BPH was 5.30, with AUCs of 0.893 in the training and 0.853 in the prospective validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 However, Mayer et al 31 reported that histology-based TV is related to the GS (r = 0.498, P = 0.0098), and Baba et al 9 suggested that the optimal TV cut-off value for predicting BCR was 2.8 cc (AUC: 0.690). Moreover, Castiglione et al 32 concluded that for high-risk patients with PCa, a TV >6.29 cc (AUC: 0.722) leads to CF, and Dong et al 33 reported that the optimal cut-off value for identifying the best maximum standardized uptake value (SUV max ) for high-risk patients with PCa was 9.61 (AUC: 0.828). Furthermore, Jiao et al 34 established and prospectively verified that the optimal SUV max cut-off value for discriminating clinically significant PCa from BPH was 5.30, with AUCs of 0.893 in the training and 0.853 in the prospective validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that tumor invasiveness is related to tumor volume and burden, the tumor volume is considered as an independent risk factor in biochemical recurrence of PCa ( 23 ). Therefore, volume parameters such as prostate PSMA-tumor volume (PSMA-TVp) and prostate total lesion PSMA (TL-PSMAp) are also being studied to overcome the above-mentioned limitations ( 24 , 25 ). However, there are few studies on the clinical application of tumor volume with PSMA PET/CT.…”
Section: Introductionmentioning
confidence: 99%